Dampak Pengelolaan Edu Wisata pada Pendapatan Masyarakat Desa - Muhammad Kambali; Anis Yunita Dewi (Fakultas Ekonomi dan Bisnis Islam, 2022)
Tourism object is one of the potentials of the people's economy that needs to be developed to increase people's income. The existence of a tourist attraction has a role in the income of the surrounding community, with a tourist attraction in an area will directly open up jobs for the surrounding community. The purpose of this study was to determine the impact of Edu Wisata on village community income. The population of this research is the people of Hendrosari Village who have a business around Edu Wisata Lontar Sewu Hendrosari. The type of research used is quantitative research. Data collection techniques used are questionnaires and documentation. The results of this study concluded that 29.7% of respondents stated that the existence of lontar sewn ecotourism had an impact on people's income and the remaining 70.3% were influenced by other factors that were not included in this research model. The results of this study have implications for the importance of managing Edu Wisata lontar sew as a step to increase the income of the community around Edu Wisata